SHERMAN ALEXIE’S" THE ABSOLUTELY TRUE DIARY OF A PART-TIME INDIAN” A TEXTUAL ANALYSIS - Amjad Khalid Khan; Majid Ali; Muhammad Rafique; Riffat Batool (International Journal of Contemporary Issues in Social Sciences, 2024)
Sherman Alexie's saga, "The Absolutely True Diary of a Part-Time Indian," emerges the pitiable narrative of Arnold Spirit Jr., or Junior, a Native American teenager going through the difficulties of life on the Spokane reservation. The first-person point of view gives an intense view in to Junior's scuffle, goal, and his double life existence in two dissimilar worlds. The story, plunged in self-effacing humor paints a clear picture of the challenges faced by Junior's community—poverty, alcoholism, and limited opportunities. As Junior goes beyond the shackles of his reservation to continue education at Reardan, the novel burrow’s into themes of identity, community spirit, and the heartfelt influence of the cultural heritage on a single person’s journey. Through satirical elucidations and a special mixture of tragedy and laughter, Alexie inspects the plasticity of the human spirit among change. The juxtaposition of Junior's experiences underscores the intricate interplay between community, personal growth, and the pursuit of a better life. This research report abstract encapsulates the multidimensional narrative of "The Absolutely True Diary of a Part-Time Indian," offering a glimpse into the rich tapestry of themes woven into Alexie's masterful storytelling.